Study of the Antioxidant Activity of Azo Chalcone and Azoflavone Derivatives by DPPH and H2O2 Methods - هادي عقل خضيره; سوسن يوسف سعد; علا مصطفى; فاروق قنديل (Latakia University Journal -Basic Sciences Series, 2023)
Flavonoids have good efficacy as antioxidants due to their ability to scavenge free radicals within cells. The antioxidant activity of azochalcone derivatives (B1-B3) and azoflavone derivatives (B4-B6) based on chalcone (2E)-3-[4-(dimethylamino)phenyl]-1-(2-hydroxyphenyl)prop-2-en-1-one was studied by two methods: : Method of radical inhibition of 2,2-diphenyl-1-picrylhydrazyl (DPPH.), method of inhibition of hydrogen peroxide (H2O2) and comparison with the effectiveness of two compounds ascorbic acid and quercetin as known antioxidants. The flavonoid derivatives (B1 - B6) were prepared in the laboratory in our previous study through condensation, cyclization, dialysis and coupling reactions, and the structural structures of the new compounds were determined using spectroscopic methods (13C-NMR, 1H-NMR, FT-IR). The inhibition ability of flavonoids was determined in four different concentrations (250, 500, 750, 1000 ppm) based on the concentrations of the compounds needed to reduce the absorption at 516 nm (DPPH.) and 230 nm (H2O2). The value of IC50 was estimated based on the curves of change in percentage inhibition percentages in terms of solution concentration. The results showed the effectiveness of compounds (B1, B2) as antioxidants.